2018
DOI: 10.1002/hbm.24328
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic connectivity networks underlying individual differences in control‐averse behavior

Abstract: When people sense that another person tries to control their decisions, some people will act against the control, whereas others will not. This individual tendency to control-averse behavior can have far-reaching consequences, such as engagement in illegal activities or noncompliance with medical treatments. Although individual differences in control-averse behavior have been well documented in behavioral studies, their neurological basis is less well understood. Here, we use a neural trait approach to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…While prosociality is clearly determined by situational factors as well 60,61 , recent research has demonstrated that there is a cross-situational and temporally stable individual tendency for prosociality 14,62 . The present study proposes potential neural traits affecting this tendency by uniquely revealing the temporal dynamics of resting EEG networks with millisecond resolution, thereby extending findings from research on the role of resting fMRI networks in prosociality 63,64 . It shows that an individual's propensity of how to engage the four resting EEG networks is associated with an individual's level of prosociality.…”
Section: Discussionsupporting
confidence: 54%
“…While prosociality is clearly determined by situational factors as well 60,61 , recent research has demonstrated that there is a cross-situational and temporally stable individual tendency for prosociality 14,62 . The present study proposes potential neural traits affecting this tendency by uniquely revealing the temporal dynamics of resting EEG networks with millisecond resolution, thereby extending findings from research on the role of resting fMRI networks in prosociality 63,64 . It shows that an individual's propensity of how to engage the four resting EEG networks is associated with an individual's level of prosociality.…”
Section: Discussionsupporting
confidence: 54%
“…34 It is likely that these areas do not specifically subserve vestibular processing, but rather contribute sensory input or perform integrative or output functions in concert with vestibular cortex, represented by PIVC, R SMG/PF, and 23c/CSv. For example, the posterior hippocampus has been associated with spatial localization, 59,60 whereas SEF is engaged in smooth pursuits and saccades 61,62 and R SPL/7m and cingulate areas 31, 32, and 33 have been identified as components of the salience, 63,64 central executive, 63,64 and default mode networks. 65,66 F I G U R E 3 Subgraphs in the adjacency matrix of connections common to all participants.…”
Section: Discussionmentioning
confidence: 99%
“…The aCC in a circuit compelling the aINS and substantia nigra (SN) will also leave its imprints in decision-making processes stirring social behavior. Here, the aCC will play a role in the maintenance of the cognitive sets required for a task or interaction, influencing reaction to exogenous influences on one's freedom of choice [4,5,37].…”
Section: Extraversion and Neuroticismmentioning
confidence: 99%
“…Furthermore, connectivity between the vmPFC, INS, caudate and NAcc has been observed in prospective reasoning, or anticipation of future outcomes of decision, with reduced INS CTh being observed in individuals presenting reduced levels of empathy [33,58]. A completion of this circuit in the particular aspect of one's valuing of communal needs can be accomplished by adding the AM and aCC to this equation, with the dorsal-aCC playing an import role in controlling adverse behavior and resistance to framing [4,59]. These two ROIs have been linked to the identification of goals and behaviors aiming to serve self-well-being in a social group-often linked to survival in hominids and other social animals [33].…”
Section: Agreeableness and Conscientiousnessmentioning
confidence: 99%
See 1 more Smart Citation